Phototherapy and serum calcium levels in full term neonates with hyperbilirubinemia - Carissa Lidia; I Made Kardana; Gusti Ayu Putu Nilawati; Ida Bagus Subanada; I Gusti Agung Ngurah Sugitha Adnyana; Ayu Setyorini Mestika Mayangsari (Indonesian Pediatric Society, 2021)
Background Hyperbilirubinemia is one of the most common problems in newborns. Severe hyperbilirubinemia, known as kernicterus, can suppress O2 consumption and oxidative phosphorylation, as well as damage brain cells, resulting in neuronal dysfunction and encephalopathy. Phototherapy is a common therapy for neonatal hyperbilirubinemia, but may rarely lead to the adverse effect of hypocalcemia. Objective To investigate serum calcium levels in full term neonates with hyperbilirubinemia, before and after phototherapy. Methods This cohort study compared total serum calcium level before and after phototherapy in full term neonates with hyperbilirubinemia. Subjects were full term neonates aged 2-14 days with high total serum bilirubin levels, according to the Bhutani curve, and were treated with phototherapy at Sanglah Hospital, Denpasar, Bali, Indonesia. Paired T-test was used to compare serum calcium levels before and after phototherapy. Results There were 35 subjects in this study. Paired T-test revealed that subjects’ serum calcium significantly decreased after phototherapy [before: 9.47 mg/dL vs. after: 9.23 mg/dL; mean difference 0.24; (95%CI 0.03 to 0.46; P=0.025)]. None of our subjects had hypocalcemia after phototherapy. Conclusion Full term neonates with hyperbilirubinemia have reduced serum calcium levels after phototherapy.